The Adsorption Properties of Bacillus atrophaeus Spore on Functionalized Carbon Nanotubes. (4th August 2010) - Cortes, P.; Deng, S.; Camacho, L.; Smith, G. B.
Abstract : An equilibrium study of Bacillus atrophaeus ( B.a ) spores on functionalized Single-Wall Carbon Nanotubes (SWCNTs) has been performed in order to characterize the adsorption properties of the spores/nanotubes complex. The carbon nanotubes here investigated were subjected to a two-step purification and functionalization treatment in order to introduce chemical groups on their basal planes. The inclusion of carboxyl functional groups on the nanotubes was corroborated by Raman and infrared spectroscopy. These carboxyl groups appear to enhance the nanotube- B.a. interaction by reacting with the proteinaceous pili appendages present on the spore surface. The adsorption data demonstrate that bacillus spores diffuse faster on functionalized carbon nanotubes than on as-received and purified nanomaterials. Transmission Electron Microscopy also shows that the chemically treated nanotubes resulted in a swollen nano-network which seems to further enhance the bacillus adsorption due to a more extensive spore-nanotube contact area.